Nucleotide sequence and expression of the glucoamylase-encoding gene (glaA)from Aspergillus oryzae. - Yoji, H.; Kozo, T.; Katsuhiko, K.; Katsuya, G.; Chieko, K.; Gakuzo, T.; Shodo, H.
The glucoamylase-encoding gene (glaA)from Aspergillus oryzae was cloned using its cDNA as a probe, which had been isolated previously. From comparison of nucleotide (nt)sequences of genomic clones with its cDNA, the glaA gene was found to contain four short putative introns, 45-56 nt in length. The A. oryzaeglaA gene shared 62 per cent homology at the nt level with the A. nigerglaA gene with the four introns located at the same position. The 5'-flanking region contained a TATA box at nt ?72 from the start codon, and two putative CAAT sequences at nt ?87 and ?331. Genomic Southern analysis and physical mapping showed that the glaA gene is located on the smallest chromosome (3.4 Mb)of six separated bands of chromosomes. Clones containing the glaA gene, when re-introduced intro A. oryzae, resulted in a three- to eightfold increase in glucoamylase activity.
Keywords: RECOMBINANT DNA; INTRON; TRANSFORMATION; GENE STRUCTURE; PHYSICAL MAPPING; SAKE; ASCOMYCETES